Measuring Vitamin D level in the Human Serum at Basra City (Southern of Iraq) - Abdulkareem, Entehaa.; H. Ibrahim, Ali; F. Hussein, Ali; Khan, Moahamad (International Journal of Psychosocial Rehabilitation, 2020)
Sunshine vitamin (vitamin D). It’s a fat-soluble prohormone, and vitamin D is very important for bone health in humans (children and adults). It’s synthesized in response to sunlight. The aim of the study was to measure the level of vitamin D in the human body by collecting 100 individuals of patients in different sites of Basra city (southern Iraq) during the period from the 1st of September to the 31st of December, 2019. The patient age range started from 5 months up to 62 years. Each sample was examined by the technique of ECL, which is electrochemiluminescence (Cobas e 411 analyzer, Roche Company, Germany). The study showed that 83% of patients were having abnormal levels, while 17% of patients were normal or sufficient. 82% of patients had a low level of vitamin D; only 1% of patients had a very high level of vitamin D (toxic). There are 63% out of 82% who had insufficiency and 19% who had deficiency. The normal level of vitamin D must be any number between 30 and 80 ng/mL and is essential to keep a healthy body. Between 10 and 30 ng/mL is considered insufficient, and below 10 ng/mL is deficient. The increase of vitamin D level over 80 ng/mL is poison. The deficiency of vitamin D levels detailed the highest rate (6 cases) in ages 20–29 and 40–49 years. Both ages (1 day-9 years and 60 and over) do not have any deficiency, whereas the highest rate (18 cases) in age (20-29) years was insufficiency in vitamin D level, and one case in age (60 and over) was the lowest. The high level of vitamin D is for just one case, which was 46 years old.